The present in retrospect: Press reporting of UK General Elections, 1918–2015. (August 2019) - Deacon, David; Harmer, Emily
This article provides a unique content analysis of 100 years of national press coverage of UK General Elections and tests four claims about historical trends in election news reporting in democratic systems: (1) that coverage is becoming more focussed on political leaders at the expense of other political sources; (2) that reporting of the personalities and personal lives of politicians has expanded; (3) that editorial treatment of politicians has become increasingly negative and (4) that news coverage is increasingly obsessed with the conduct of politics rather than its substantive content. Through the detail of this analysis, we identify areas of historical continuity as well as change and challenge overly neat periodisations and simple histories of election news reporting.